The SAGE handbook of environment and society - Pretty, Jules N.; SAGE Knowledge (Online service). (Los Angeles, [Calif.] London SAGE, 2007)
Focusing on the interactions between people, societies and economies, and the state of nature and the environment, this text presents readers in social science and natural science with a manual of the past, present and future of environment-society links.
Includes bibliographical references and index.
Keywords: Environmental sciences; Nature -- Effect of human beings on; Human ecology; Electronic books